Insulation vs. Dissolution. An Interview with Eric Kraft - Francisco Collado Rodríguez (Miscelánea: A Journal of English and American Studies)
The New York novelist Eric Kraft tells in this interview about his main literary sources (Nabokov, Barth), and comments on some of the aspects that make his fiction a very interesting combination of metafictional writing and accurate realism. Aspects such as the notion of a postmodern realism, insulation vs. fuzziness, quantum mechanics and chaos theory, or the role of the reader combine with other comments on specific contemporary issues such as the value of electronic books or the necessity to improve readership among young people.